2013
DOI: 10.1073/pnas.1220674110
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of TBK1 signaling via phosphoproteomics in lung cancer cells

Abstract: TANK-binding kinase 1 (TBK1) has emerged as a novel therapeutic target for unspecified subset of lung cancers. TBK1 reportedly mediates prosurvival signaling by activating NF-κB and AKT. However, we observed that TBK1 knockdown also decreased viability of cells expressing constitutively active NF-κB and interferon regulatory factor 3. Basal phospho-AKT level was not reduced after TBK1 knockdown in TBK1-sensitive lung cancer cells, implicating that TBK1 mediates unknown survival mechanisms. To gain better insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 37 publications
8
99
0
Order By: Relevance
“…TBK1 is also linked to the maintenance of basal autophagy which promotes non-canonical NF-kB signaling in KRAS-mutant NSCLC cells, raising the possibility of targeting autophagy for KRAS mutant lung cancer treatment [12]. Recently, our study demonstrated that TBK1 activity is regulated in a cell cycle-dependent manner, phosphorylates Polo-like kinase 1 (PLK1) at G2/ M in TBK1-dependent KRAS mutant NSCLC cell lines, suggesting the importance of TBK1 in cell cycle progression in cancer (Figure 1; Left panel) [13].…”
Section: Role Of Ikke/tbk1 In Lung Cancermentioning
confidence: 79%
See 1 more Smart Citation
“…TBK1 is also linked to the maintenance of basal autophagy which promotes non-canonical NF-kB signaling in KRAS-mutant NSCLC cells, raising the possibility of targeting autophagy for KRAS mutant lung cancer treatment [12]. Recently, our study demonstrated that TBK1 activity is regulated in a cell cycle-dependent manner, phosphorylates Polo-like kinase 1 (PLK1) at G2/ M in TBK1-dependent KRAS mutant NSCLC cell lines, suggesting the importance of TBK1 in cell cycle progression in cancer (Figure 1; Left panel) [13].…”
Section: Role Of Ikke/tbk1 In Lung Cancermentioning
confidence: 79%
“…Targets (2013) 17(10) the loss of key survival kinases by inducing alternative survival signaling resulting in adaptive resistance. Our recent study revealed that loss of TBK1 leads to compensatory activation of receptor tyrosine kinases in lung cancer cells [13]. Adaptive response could attenuate the efficacy of the kinase inhibition or induce innate resistance.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Besides its key role in innate immune response, increasing evidence indicates that the activation of TBK1 and its close homolog IKKe is associated with the development of human cancers (2)(3)(4)(5)(6)(7)(8)(9)(10). TBK1 is an 84 kDa, 729 amino acid-long protein containing an N-terminal kinase domain, a ubiquitin-like domain and two C-terminal coiled-coil domains.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22]. IRF3 phosphorylation at residues Ser-385 and Ser-386 has previously been shown to control its dimerization (23)(24)(25) upon which IRF3 translocates to the nucleus (26), and controls transcriptional regulation of cell survival and proliferation (2,11). In addition to IRF3, several other substrates, i. e., namely cRel, Akt, RalB, SIKE, etc., have been identified that attribute to TBK1 function (7)(8)(9)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…They establish that loss of MTDH leads to PARP cleavage and diminished cell viability. In addition, they performed shRNA-mediated knockdown of MTDH, TBK1, and KRAS in 14 lung cancer cell lines with detail EGFR and KRAS mutation status 45 .…”
Section: Fig 1: Various Biological Functions and Potential Lead Molementioning
confidence: 99%